MEMBANGUN KESADARAN HUKUM MELALUI PENYUSUNAN STANDAR PELAYANAN PADA KANTOR KELURAHAN MARICAYA - Adam, Ainunnisa; Maulida, St. Nurhikma (ADMIT: Jurnal Administrasi Terapan, 2024)
Bureaucratic reform is one of the stages  to improve the quality of public services in achieving the vision of Advanced Indonesia in 2045. The implementation of clear and measurable service standards is the basis for ensuring that every stage of service leads to better public services and in accordance with community expectations. As a basic level public service provider, the Makassar City Maricaya Village Office has not yet fulfilled its responsibility to develop service standards and implement them in the service delivery process. This makes it difficult for the community to obtain service guarantee regarding the requirements, time, and costs required in completing the service. So it is necessary to compile and implement service standards with the aim of providing certainty and information disclosure to the public regarding public service delivery. This research used a qualitative approach by collecting data through observation, interviews, document review and Focus Group Discussion methods. The preparation of service standards in this study involved public service officers and several service users at the Maricaya Village Office. The service standards prepared are guided by Regulation of Minister of Ministry of State Apparatus Utilization and Bureaucratic Reform Number 15 of 2014 concerning Service Standard Guidelines. The draft service standards that have been made and agreed upon are then determined by the Maricaya Village Head to be applied in the implementation of public services at the Maricaya Village Office. The work in the form of Service Standards for letter of poverty statement, Business Certificate and Death Certificate is the final result of this research.